Job stability for kindergarten teachers (Journal of the College of Basic Education, 2022)
The current research aims to identify the job stability of kindergarten teachers, and the research relied on the descriptive approach, and the research sample was (250) kindergarten teachers in Najaf Governorate. On the subject of their research, as the job stability measure in its final form included (45) items, and the two researchers verified the psychometric characteristics of the tool. The two researchers reached the following results:Kindergarten teachers have job stability.The years of service at its different levels and the educational qualification at its different levels have nothing to do with job stability for kindergarten teachers.